Role of fibroblasts in wound healing and tissue remodeling on Earth and in space - Cialdai, Francesca; Risaliti, Chiara; Monici, Monica (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing (WH) and the role fibroblasts play in the process, as well as healing impairment and fibroblast dysfunction, have been thoroughly reviewed by other authors. We treat these topics briefly, with the only aim of contextualizing the true focus of this review, namely, the microgravity-induced changes in fibroblast functions involved in WH. Microgravity is a condition typical of spaceflight. Studying its possible effects on fibroblasts and WH is useful not only for the safety of astronauts who will face future interplanetary space missions, but also to help improve the management of WH impairment on Earth. The interesting similarity between microgravity-induced alterations of fibroblast behavior and fibroblast dysfunction in WH impairment on Earth is highlighted. The possibility of using microgravity-exposed fibroblasts and WH in space as models of healing impairment on Earth is suggested. The gaps in knowledge on fibroblast functions in WH are analyzed. The contribution that studies on fibroblast behavior in weightlessness can make to fill these gaps and, consequently, improve therapeutic strategies is considered.